Conductance through a Ti-atom impurity in Ag(100) and Au(111): a ionic model considering spin fluctuations - Romero, Marcelo Ariel (2013)
We describe the interaction between a transition-metal atom and a noble-metal surface by using an ionic model in which the first Hund's rule determines the filling of the atom's d levels, and spin fluctuations occur due to the electron exchange between the metal band and the atom states. We apply our model to the case of adsorbed Ti atoms on noble-metal surfaces (Ag and Au) in which conductance measurements in scanning tunneling microscope experiments suggest a mixed-valence regime according to the position and width of the atomic resonance. By introducing, in our calculation, these two parameters as extracted from the experiment, we satisfactorily reproduce the experimental results in both cases. We find, in the Ag(100) surface, that the conductance spectrum reflects electronic characteristics of the metal surface modified by the presence of the magnetic atom; whereas, in the Au(111) case, only the projected density of states on the Ti atom determines the conductance spectrum shape.